Heavy vs light load single-joint exercise performance with different rest intervals - Weber Senna, G.; Minelli Rodrigues, B.; Sandy, D.; Scudese, E.; Bianco, A.; Martin Dantas, E. H. (Journal of Human Kinetics, 2017)
The aim of the study was to compare the effect of three distinct rest period lengths between sets of upper body single-joint exercise with different load zones and volume designed for either endurance or hypertrophy (50% or 80% of 1-RM). Sixteen trained men (20.75 ± 2.54 years; 76.35 ± 5.03 kg; 176.75 ± 3.33 cm, 24.53 ± 1.47 kg/m2) performed a test and retest of 1-RM on non-consecutive days. Forty-eight hours after load testing, the participants were randomly assigned to six sessions consisting of four sets of the triceps pull-down, combining different intensities with distinct rest periods between sets. The shorter 1 minute rest promoted a significant reduction in the total repetition number compared to 3 minute rest for both workloads. There was a difference between 3 and 5 minute conditions for the 50% of 1-RM that did not occur for the 80% of 1-RM condition. Both intensities presented significant interaction values for the rest conditions vs. each set (50% p = 0.0001; 80% p = 0.0001). Additionally, significant values were found for the main effect of the performance of subsequent sets (50% p = 0.003; 80% p = 0.001) and rest conditions (50% p = 0.0001; 80% p = 0.0001). In conclusion, for heavier loads (80%) to fatigue, longer rest of 3 to 5 minutes seems to allow for better recovery between sets and thus, promotes a greater volume. However, when training with lighter loads (50%), the magnitude of the rest seems to directly affect the performance of subsequent sets, and also presents a correlation with total volume achieved for the upper body single-joint exercise scheme.